Regioselective Deacetylation of Disaccharides via Immobilized Aspergillus niger Esterase(s)‐catalyzed Hydrolysis in Aqueous and Non‐aqueous Media. Issue 10 (26th July 2013) - Bavaro, Teodora; Torres‐Salas, Pamela; Antonioli, Nicola; Morelli, Carlo F.; Speranza, Giovanna; Terreni, Marco
Abstract Purified lipase fractions from crude commercial extract of Aspergillus niger lipase (ANL) were selectively immobilized on hydrophobic supports. A significant percentage of esterase activity remains in the supernatant, derived from esterase(s) unable to become adsorbed onto the employed matrices. These residual proteins were covalently immobilized on epoxy‐acrylic resin. Immobilized hydrolases were tested in the hydrolysis of acetylated disaccharides in water‐cosolvent systems. ANL‐Esterase was able to catalyze regioselective deprotection of acetylated β‐O‐methyl lactoside in C‐2 position and β‐O‐methyl lactosaminide in C‐3′ position. The hydrolyzed products, never reported before, can be considered new building blocks for the synthesis of oligosaccharides of biological relevance. Furthermore, preparative hydrolyses were also performed in tert‐butanol. This solvent is compatible with ANL‐esterase stability and it appears to be a novel and promising approach because of its green status.